16.5k views
0 votes
3x+4(x+3)=7 solve for x

User Davislor
by
5.0k points

2 Answers

6 votes
3x+4(x+3)=7
3×+4×+12=7
7×+12=7
7×=-5
×=-5/7
User George Chen
by
4.9k points
4 votes

Answer:

x =
(-5)/(7)

Explanation:

Step 1: Simplify both sides of the equation.

3x+4(x+3)=7

3x+(4)(x)+(4)(3)=7(Distribute)

3x+4x+12=7

(3x+4x)+(12)=7(Combine Like Terms)

7x+12=7

7x+12=7

Step 2: Subtract 12 from both sides.

7x+12−12=7−12

7x=−5

Step 3: Divide both sides by 7.


(7x)/(7) = (-5)/(7)


User Rytis
by
5.0k points